Cloning, expression, and characterization of coenzyme-B₁₂-dependent diol dehydratase from Lactobacillus diolivorans - Wei, Xuqin; Meng, Xiaolei; Chen, Yunlai; Wei, Yutuo; Du, Liqin; Huang, Ribo (Biotechnology letters, 2014)
The three gldCDE genes from Lactobacillus diolivorans, that encode the three subunits of the glycerol dehydratase, were cloned and the proteins were co-expressed in soluble form in Escherichia coli with added sorbitol and betaine hydrochloride. The purified enzyme exists as a heterohexamer (α₂β₂γ₂) structure with a native molecular mass of 210 kDa. It requires coenzyme B₁₂ for catalytic activity and is subject to suicide inactivation by glycerol during catalysis. The enzyme had maximum activity at pH 8.6 and 37 °C. The apparent K ₘ values for coenzyme B₁₂, 1,2-ethanediol, 1,2-propanediol, and glycerol were 1.5 μM, 10.5 mM, 1.3 mM, and 5.8 mM, respectively. Together, these results indicated that the three genes gldCDE encoding the proteins make up a coenzyme B₁₂-dependent diol dehydratase and not a glycerol dehydratase.